Long-Term, Multicountry Perspective on Rental Market Regulations - Konstantin Kholodilin (Housing Policy Debate, 2020)
This study introduces a new international longitudinal database of governmental rental market regulations. The regulations are measured using binary variables based on a thorough analysis of real-time, country-specific legislation. Three major restrictive policies are considered: rent control, protection from restriction, and housing rationing. The database covers 101 countries and states between 1910 and 2020. This allows comparisons of regulation intensity across both time and space. The analysis reveals a surge in restrictive policies in the first half of the 20th century. However, following World War II, the evolution of policies diverged: whereas rent control became more flexible or was phased out, tenure security stabilized at a high level or even increased, and housing rationing became used less frequently.
Keywords: 330; rental regulation indices; rent control; tenure security; housing rationing